A signalling theory of scapegoats - Björn Segendorff (Stockholm School of Economics, The Economic Research Institute (EFI), 2000)
This study investigates under what circumstances there exist a separating equilibrium in which competent leaders choose incompetent co-workers and incompetent leaders choose competent co-workers. The driving force for the competent leader is the insurance motive; if things go wrong he can blame the incompetent co-worker and remain his reputation of being competent. For the incompetent leader the expected gain from such an insurance is outweighed by its costs in terms of lower expected policy outcome. Co-workers are motivated by career opportunities allowing for conflicting interests between the leader and the co-worker.
Keywords: C72; D72; D82; J33; 330; Separating equilibrium; competence; co-worker; blame; scapegoat